2017
DOI: 10.3329/agric.v15i1.33436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage Practices and Rice Straw Management on Soil Environment and Carbon Dioxide Emission

Abstract: Carbon (C) inputs and tillage intensity impinge on C degradation and thus CO 2 emission and soil properties get influenced. Information on CO 2 emission and soil properties under different tillage practices and straw application in rice based cropping system in Bangladesh is lacking. The effects of rice straw and tillage operations on CO 2 emission and soil properties were quantified in four consecutive seasons of transplanted Aman and Boro rice grown under two tillage operations (minimum and traditional) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Adoption of resource conservation strategies and best management practices might ensure supply and maintenance of organic matter in soils. It is reported that reduced tillage combined with rotations or cover crops that include deep rooted and high residue producing plants is most effective to enhance soil organic matter in soils (Franzluebbers, 2010, Rahman et al, 2017. Organic matter governs bio-physico-chemical properties of soils and thus maintains and regulates soil quality and nutrient cycling.…”
Section: Carbon Stock In Soils Of Purbadhola and Akhaura Upazila And mentioning
confidence: 99%
“…Adoption of resource conservation strategies and best management practices might ensure supply and maintenance of organic matter in soils. It is reported that reduced tillage combined with rotations or cover crops that include deep rooted and high residue producing plants is most effective to enhance soil organic matter in soils (Franzluebbers, 2010, Rahman et al, 2017. Organic matter governs bio-physico-chemical properties of soils and thus maintains and regulates soil quality and nutrient cycling.…”
Section: Carbon Stock In Soils Of Purbadhola and Akhaura Upazila And mentioning
confidence: 99%
“…Water imponding and no water imponding were not much differed in emission of CO 2 from field throughout crop period and observed higher emission in initial first 15 days after transplanting which was higher with water imponding of 40 days, 10 days after transplanting (2465.31 g day -1 ha -1 ) being at par to hand weeding twice (2409.14 g day -1 ha -1 ) and no water imponding (2284.81 g day -1 ha -1 ) (Table 4). Rahman et al, (2017) observed that reduced tillage also can play an important role in accumulating carbon in the soil. The soil is a major source of emission for atmospheric CO 2 content.…”
Section: Effect Of Agronomical Manipulations On Co 2 Emissionmentioning
confidence: 99%
“…Management of home garden in the form of tillage, mulching, and soil compaction may be another driving force for C exchange 48 50 . The variation in SOC stock is influenced by addition and removal of biomass due to management activities, an underlying processes in the soil 51 , 52 .…”
Section: Introductionmentioning
confidence: 99%